Effect of serum progesterone levels on hCG trigger day on pregnancy outcomes in GnRH antagonist cycles - Zhang, Junwei; Du, Mingze; Wu, Yanli; Wei, Zhancai; Guan, Yichun (Frontiers in Endocrinology, 2022)
Objective: To analyze the effect of hCG trigger day progesterone (P) levels on live birth rate (LBR) in the GnRH antagonist protocol. Materials and methods This was a retrospective study. IVF/ICSI cycles conducted from January 2017 to December 2020 were included in the analysis. This study included people with a normal ovarian response to fresh embryo transfer of GnRH antagonist protocols. All cycles were divided into 2 groups by P level on the day of hCG trigger, P<1.0 ng/ml and P≥1.0 ng/ml. The primary outcome measure was LBR. Result 867 cycles with P<1.0 ng/ml and 362 cycles with P≥1.0 ng/ml were included in the analysis. The CPR was higher in the P<1.0 ng/ml group than in the P≥1.0 ng/ml group (44.9% vs. 37.6%, P=0.02). The early spontaneous abortion rate was comparable between the groups (14.4% vs. 14.7%, P=0.93). For live birth, the rate of P<1.0 ng/ml was 35.3%, which was significantly higher than the 29.0% in the P≥1.0 ng/ml group (P=0.03). After binary logistic regression analysis, the P level on the hCG trigger day (AOR=0.74, 95% CI=0.56-0.97, P=0.03) was an independent risk factor for LBR. In other words, for the P level on the hCG trigger day, compared with the P<1 ng/ml group, the LBR was lower in the P≥1.0 ng/ml group. Conclusion For normal ovarian response patients with the GnRH antagonist protocol, serum P≥1.0 ng/ml on the HCG trigger day resulted in a lower LBR than P<1 ng/ml. When P≥1.0 ng/ml, whole embryo freezing can be considered.